NCERT Solutions for CBSE Class 12 Mathematics ‒ Chapter 1: Relations and Functions (Part V)

NCERT Solutions for CBSE Class 12 Maths, Chapter 1: Relations & Functions are available in this article. Here, you will get solutions to the questions of exercise 1.3 from question number 8 to question number 14. These questions are related to composition of functions and invertible function.

NCERT Solutions for CBSE Class 12th Maths, Chapter 1: Relations and Functions (Exercise 1.3) are given below

Question8:


Solution 8:


NCERT Exemplar Class 12 Mathematics – Chapter 1 Relations and Functions

Question 9:


Solution 9:


NCERT Solutions for CBSE Class 12 Physics: All Chapters

Question 10: Let f : X → Y be an invertible function. Show that f has unique inverse. (Hint: suppose g1 and g2 are two inverses of f. Then for all y ∈ Y, fog1(y) = IY(y) = fog2(y). Use one-one ness of f).

Solution 10:

Let Y is an invertible function

Suppose g1 & g2 are two inverses of f

Now, for all y ϵ Y,

fog1 (y) = fog2 (y)

f[g1(y)] = f[g2(y)]

g1(y) = g2(y) {f is one-one}

Trending Now

g1 = g2 (g is one-one)

Question 11: Consider f : {1, 2, 3} → {a, b, c} given by f (1) = a, f (2) = b and f (3) = c. Find f –1 and show that (f –1)–1 = f.

Solution 11:

f: {1, 2, 3} → {abc}

f(1) = a 

f(2) = b 

 f(3) = c

Let g: {abc} → {1, 2, 3}

g(a) = 1

g(b) = 2

g(c) = 3

Now,

(fog) (a) = f [g(a)] = f (1) = a

(fog) (b) = f [g(b)] = f(2) = b

(fog) (c) = f [g(c)] = f (3) = c

(gof) (1) = g [f(1)] = g(a) =1

(gof) (2) = g [f(2)] = g(b) =2

(gof) (3) = g [f(3)] = g(c) =3

Thus, gof = fog

gof  = IX

fog = IY

Where X = {1, 2, 3} and Y= {abc}

Thus, f−1 = g

Hence, f−1: {abc} → {1, 2, 3}

f−1(a) = 1

f−1(b) = 2

 f-1(c) = 3

Let us calculate the inverse of f−1 

h: {1, 2, 3} → {abc}

h(1) = ah(2) = bh(3) = c

Then,

(goh) (1) = g[h(1)] = g(a) = 1

(goh) (2) = g[h(2)] = g(b) = 2

(goh) (3) = g[h(3)] = g(c) = 3

(hog)(a) = h [g(a)]= h (1) = a

(hog)(b) = h [g(b)]= h (2) = b

(hog)(c) = h [g(c)]= h (3) = c

goh = IX

hog = IY

Now,

g−1 = h 

(f−1)−1 = h

We can observe that

 h = f

Hence, (f‒1)‒1 = f.

Question 12: Let f : X → Y be an invertible function. Show that the inverse of f–1 is f, i.e., (f –1)–1 = f.

Solution 12:


Question 13: If f : R → R be given by f (x) = (3 − x3 )1/3 , then fof (x) is

(A) x3

(B) x3

(C) x

(D) (3 – x3).

Solution 13:


Question 14:

Solution 14:

Download NCERT Solutions for Class 12 Maths: Chapter 1 Relations and Functions in PDF format

Related Categories

Live users reading now